EFFICACY OF CURCUMIN AND MONOCHROMATIC LIGHT IN IMPROVING LIVER FUNCTIONS OF SEXUALLY MATURE MAGELANG DUCKS - Kasiyati, K.; Manalu, W.; Sumiati, S.; Ekastuti, D. R. (Diponegoro University, 2016)
The liver of female poultry has a vital role as an organ for biosynthesis of the yolk precursor and has a greater chance of experiencing cellular damages. This experiment was designed to study the uses of curcumin and monochromatic light in suppressing liver destruction during the period of yolk biosynthesis in Magelang ducks. One hundred and ninety two female Magelang ducks were assigned into a completely randomized design with a 4x4 factorial arrangement. The first factor was dose of curcumin supplementation consisted of 4 levels i.e., 0, 9, 18, and 36 mg. The second factor was the color of monochromatic light consisted of 4 levels i.e., white, red, green, and blue. The results showed that hydropic and fat degenerations in the livers of Magelang ducks entering laying phase were still in a normal range. There was an interaction effect between curcumin and monochromatic light on the serum SGPT/GOT and liver MDA concentrations (P<0.05). Serum lipid concentrations positively correlated with the increased serum SGPT/GOT and liver MDA concentrations as indicators of liver damages. Supplementation of curcumin and the use of monochromatic light could reduce and suppress liver destruction and damage during laying period.